Public perception of radio campaign messages in managing COVID-19 pandemic in selected states, Nigeria - Felix Olajide Talabi; Kazeem Alade Oyedeji; Omowale Adelabu; Bernice O. Sanusi; Tokunbo Adaja; Joseph Moyinoluwa Talabi; Samson Adedapo Bello; Ishola Kamorudeen Lamidi; Moyosore Alade (Taylor & Francis Group, 2022)
The study examined public perception of Nigeria Center of Disease Control's (NCDC) radio campaign messages in managing the Covid-19 pandemic in three selected states in the south-western part of the country. A survey research design was adopted with a questionnaire as a data collection instrument. A sample size of 400 respondents was chosen through the multistage approach. The study revealed that the residents in selected states in South-Western Nigeria reported exposure to radio campaign messages on COVID-19 preventive measures and perceived that the messages influenced the awareness and adoption of COVID-19 preventive measures. It was recommended that behavioral change communication experts and public health officers at all levels should leverage the reliability and spread of radio among the populace to disseminate public health issues.